Governance structure, technical change and industry competition - Mattia Guerini; Philipp Harting; Mauro Napoletano (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
We develop a model to study the impact of corporate governance on firm investment decisions and industry competition. In the model, governance structure affects the distribution of shares among short- and long-term oriented investors, the robustness of the management regarding possible stockholder interference, and the managerial remuneration scheme. A bargaining process between firm's stakeholders determines the optimal allocation of financial resources between real investments in R&D and financial investments in shares buybacks. We characterize the relation between corporate governance and firm's optimal investment strategy and we study how different governance structures shape technical progress and the degree of competition over the industrial life cycle. Numerical simulations of a calibrated set-up of the model show that pooling together industries characterized by heterogeneous governance structures generate the well-documented inverted-U shaped relation between competition and innovation.
Keywords: G34; L22; M12; 330; governance structure; industry dynamics; competition; technical change